The effects of environmental regulation on chemical industry location: Evidence from the region along the Yangtze River, China. (21st January 2022) - Zou, Hui; Duan, Xuejun; Wang, Lei; Jin, Tingting
Abstract: Environmental regulation is an important factor affecting the relocation of polluting industries. This study explores the spatial pattern evolution of the chemical industry, regional differences in environmental regulation, and the corresponding pollution haven effect in the region along the Yangtze River from 2000 to 2013. We found that the distribution of the chemical industry had shifted from developed regions (downstream regions) to developing regions (middle and upper reaches) reflecting the emergence of pollution paradise effects. This is mainly due to differences in the level of government enforcement and public supervision. Based on the spatial relationship analysis, the pollution haven effect is divided into two stages (i.e., irresolution and continuous effective), reflecting the process of environmental regulation from a failure to inhibit the growth of the chemical industry (before 2004) to significant inhibition (after 2009, when the provincial governments in the lower reaches took serious steps to improve environmental regulation), thereby promoting the transfer of the chemical industry from downstream to upstream. This study provides evidence from China, leading to a better understanding of environmental regulation and the pollution haven effect for the chemical industry, which is representative of other polluting industries and developing countries.